Dispersion Effect in Left-Turning Bicycle Traffic and Its Influence on Capacity of Left-Turning Vehicles at Signalized Intersections. Issue 1 (January 2014) - Chen, Jingxu; Wang, Wei; Li, Zhibin; Jiang, Hang; Chen, Xuewu; Zhu, Senlai
Bicycle traffic passing through intersections exhibits a dispersion effect that can influence the movements of nearby vehicles. The primary objective of this study was to investigate the dispersion effect in left-turning bicycle traffic at signalized intersections and to evaluate the effect's influence on the capacity of left-turning vehicles. Characteristics of the dispersion effect were investigated in 20 h of video data collected in Nanjing, China. A Poisson model was estimated to evaluate the factors contributing to platoon width of left-turning bicycle traffic. The impacts of platoon width on the capacity and delay of left-turning vehicles also were evaluated. Results showed that several factors, including the number of left-turning electric bicycles (e-bicycles) and conventional bicycles arriving during the red light period and the directional factor, significantly affected the platoon width of left-turning bicycle traffic. Sensitivity analysis results indicated that the platoon was widest when the number of left-turning e-bicycles divided by the number of total left-turning bicycles arriving per cycle was about 60%. An adjustment factor that accounted for the impacts of left-turning bicycles on the capacity of left-turning vehicles was proposed. Increasing the platoon width of left-turning bicycles from three to eight reduced the left-turning vehicle capacity about 19% and increased the capacity of all left-turning traffic around 25%.